Temporal Lobe Epilepsy Semiology - Blair, Robert D. G. (Hindawi Publishing Corporation, 2012)
Epilepsy represents a multifaceted group of disorders divided into two broad categories, partial and generalized, based on the seizure onset zone. The identification of the neuroanatomic site of seizure onset depends on delineation of seizure semiology by a careful history together with video-EEG, and a variety of neuroimaging technologies such as MRI, fMRI, FDG-PET, MEG, or invasive intracranial EEG recording. Temporal lobe epilepsy (TLE) is the commonest form of focal epilepsy and represents almost 2/3 of cases of intractable epilepsy managed surgically. A history of febrile seizures (especially complex febrile seizures) is common in TLE and is frequently associated with mesial temporal sclerosis (the commonest form of TLE). Seizure auras occur in many TLE patients and often exhibit features that are relatively specific for TLE but few are of lateralizing value. Automatisms, however, often have lateralizing significance. Careful study of seizure semiology remains invaluable in addressing the search for the seizure onset zone.